Comparative analysis between single incision and conventional laparoscopic appendectomy for acute appendicitis - Sateesh, Sreeram; Subraj, Harsha; Mahesh, Gangaiahgari; Rao, Pasupuleti Sreenivasa (International Journal of Research in Medical Sciences, 2017)
Appendicitis is an acute inflammatory condition of appendix. Since it is a surgical emergency, needs early diagnosis and treatment strategies which include clinical examination, followed by Laboratory investigations and Imaging studies. The scoring systems like Alvarado score have been considered for better diagnosis. In most studies surgery has been reported as the best modality of treatment. Several studies clearly mentioned the impact of various surgical procedures which include Open appendectomy (OA), Conventional laparoscopic appendectomy (CLA) and Single incision laparoscopic appendectomy (SILA). Hence, the present study is carried in an aim to assess and compare the merits and demerits between the surgical procedures Like SILA and CLA. The patients were randomly selected from the surgical department (NMCH) who presented with acute pain abdomen and diagnosed as acute appendicitis. 50 patients were enrolled in the study after fulfilling the inclusion and exclusion criteria. The various demographic variables have been studied between the surgical procedures to demonstrate their impact, which include wound infection rate, pain scores at 24 and 48hrs, the amount of time period for surgery in minutes, patient satisfaction scores and post-operative stay tenure at the hospital in days. The laparoscopic hand instruments used in both techniques are similar, except covidien port which was reused in SILA, following gas sterilization to reduce the cost. Findings reveal that the pain score was significantly lower in SILA than CLA group. The procedure time is comparatively more in SILA than CLA group. Patients had significant satisfaction score in SILA measured at 6 weeks after appendectomy. However the post operative stay, wound infection rate was almost similar in both the groups. There was no conversion to open Appendectomy performed in either of these groups. Results also clearly suggest that the SILA procedure is the safe, alternative and effective technique for the better management of acute appendicitis and seems to be better choice.